2010
DOI: 10.1063/1.3341019
|View full text |Cite
|
Sign up to set email alerts
|

Numerical prediction of the film thickening due to surfactants in the Landau–Levich problem

Abstract: In this work numerical solutions of the dip coating problem in the presence of a soluble surfactant are shown. Predictions of film thickening as well as thickening factors are in very good agreement with published experimental data, showing that pure hydrodynamic modeling suffices to mimic the process. Our numerical solutions provide a wealth of information on the functioning of the dip coating system; they show the appearance of a second stagnation point located in the bulk phase near the dynamic meniscus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 14 publications
2
27
1
Order By: Relevance
“…In a previous paper, 8 we showed that the thickening factors larger than one detected when the coating liquid contains a soluble surfactant are mainly associated with changes in both the interfacial shape and the pressure distribution in the dynamic meniscus and not with the nonzero values detected in the tangential component of the surface stress.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…In a previous paper, 8 we showed that the thickening factors larger than one detected when the coating liquid contains a soluble surfactant are mainly associated with changes in both the interfacial shape and the pressure distribution in the dynamic meniscus and not with the nonzero values detected in the tangential component of the surface stress.…”
Section: Resultsmentioning
confidence: 96%
“…In fact, if the concentration of solute is not fixed, its value will continuously diminish due to the convective transport of surfactant towards the film region and no steady state will be achieved. Equation (8) also establishes that far away from x ¼ 0 (in the thin film region), the free surface is parallel to the solid surface.…”
Section: A Governing Equations and Boundary Conditionsmentioning
confidence: 94%
See 2 more Smart Citations
“…in LLD configuration) defined as as a function of the control parameter Λ. Comparison to equation (29) shows that the thickening factor α Fr (resp. α LLD ) is simply the ratio between the film thickness predicted by our model and the one predicted by the Frankel (resp.…”
Section: A Comparison Of Linearized and Nonlinearized Equations Of Statementioning
confidence: 99%